A heterostuctured Co3S4/MnS nanotube array as a catalytic sulfur host for lithium–sulfur batteries. (10th January 2020) - Li, Yongpeng; Jiang, Tianyi; Yang, He; Lei, Da; Deng, Xiaoyu; Hao, Ce; Zhang, Fengxiang; Guo, Junling
Abstract: Metal sulfides (MS) have been widely explored in lithium-sulfur batteries (LSB) owing to their stronger affinity with lithium polysulfide species (LPS) than carbon materials and higher electronic conductivity compared with metal oxides. However, practical application of MS based sulfur cathodes is hindered by a slow conversion of sulfur species due to limited catalytic effect of MS for redox reactions of sulfur, and by the absence of a continuous conducting network in the cathode. To address these issues, we herein report the design and fabrication of a heterostuctured Co3 S4 /MnS nanotube array grown on carbon cloth (CC@CMS-NA) as a catalytic sulfur host for high performance LSB. According to the theoretical calculations and electrochemical test, Mn dopants can tune the electronic structure of Co3 S4 to adsorb soluble LPS more effectively and engineer a catalytic heterogeneous surface to facilitate charge transport and enhance the conversion kinetics of sulfur species. Meanwhile, the 3D array structure avoids "dead" sites caused by the use of binder and conductive additive, and also provides rapid electron transport path. As a result, the CC@CMS-NA based sulfur cathodes with 3.2 mg cm −2 sulfur loading exhibits an excellent cycle performance at a current density of 2.67 mA cm −2 (95% retention of initial specific capacity after 200 cycles, namely 0.02% decay per cycle). Our work demonstrates that reasonable construction of heterogeneous structures is a promising strategy to improve the performance of MS based LSB. Highlights: A binder-free sulfur cathode of heterostructured Co3 S4 /MnS nanotube array (CC@CMS-NA) is designed and prepared. The CMS heterostructure facilitates charge transport and enhances the conversion of sulfur species. The nanotube array can avoid "dead" sites for polysulfide adsorption and provide straight electron transport path. The CC@CMS-NA/sulfur cathode with a 3.2 mg cm −2 sulfur loading shows an excellent cycle life.